#### Answer

$a^2-5a-3$

#### Work Step by Step

$f(a)=a^2-3a+8$
$g(a+3)=-2(a+3)-5=-2a-6-5=-2a-11$
Thus $f(a)+g(a+3)=a^2-3a+8-2a-11=a^2-5a-3$

Published by
Pearson

ISBN 10:
0-13417-894-7

ISBN 13:
978-0-13417-894-3

$a^2-5a-3$

$f(a)=a^2-3a+8$
$g(a+3)=-2(a+3)-5=-2a-6-5=-2a-11$
Thus $f(a)+g(a+3)=a^2-3a+8-2a-11=a^2-5a-3$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.